Determination of Pressure-Temperature Conditions of Retrograde Symplectic Assemblages in Granulites and Amphibolites - Chun-Ming Wu; Jun-Sheng Lu; Guo-Dong Wang (Global Journal of Earth Science and Engineering, 2015)
Symplectites form during post-orogenic fast uplift processes in orogenic belts, and retrograde Symplectic assemblages mainly consist of plagioclase + quartz ± orthopyroxene ± clinopyroxene in mafic granulites or plagioclase + hornblende + quartz ± biotite in amphibolites, usually rimming relict garnet porphyroblasts. Such Symplectic assemblages resulted from retrograde reactions between garnet and other peak-metamorphic minerals by nearly isothermal decompression (ITD), so the Symplectic mineral assemblages could not be at equilibrium with the relict garnet rims and thus the so-called â€œlocal equilibriumâ€ between garnet rims and the Symplectic assemblages does not exist. Thus, the P-T conditions of the Symplectic assemblages are best determined using only the Symplectic mineral compositions. This is best accomplished using garnet-free thermobarometers, i.e., two-pyroxene or hornblendeplagioclase thermometer in combination with the hornblende-plagioclase-quartz or applying the clinopyroxeneplagioclase-quartz geobarometer to minerals within the symplectites. Taking two mafic granulite samples and two amphibolite samples as examples, reasonable ITD P-T paths from the metamorphic peaks to retrogression stages have been derived, but P-T paths obtained using the relict garnet rims and the Symplectic minerals gave anomalous results. These examples demonstrate that the P-T conditions of the retrograde Symplectic assemblages cannot be estimated using chemical compositions of the decomposed, relict garnet rims in this case.